Contractual controversies from the French and Anglo-American paradigms in the Colombian contractual system (2020)
This article discerns regarding the amalgamation of systems that result in the Colombian contracting system, within which the distinction between private and public contractors that comes from the French approach, together with the application of common law to both Private contractors as well as state contractors from the Anglo-American model and their exercise of the principle of equality are unified in a multifaceted system that generates different results from their referents, which has the ability to collaborate in an improvement of the contracting conditions, contributing to the balance against which within the administrative contracts.